Rhazinilam−leuconolam−leuconoxine alkaloids from leuconotis griffithii - Kam, T.S.; Gan, C.Y.; Low, Y.Y.; Thomas, N.F. (American Chemical Society, 2013)
Eight new indole alkaloids (1–8) belonging to the rhazinilam–leuconolam–leuconoxine group, in addition to 52 other alkaloids, were isolated from the stem-bark extract of Leuconotis griffithii, viz., nor-rhazinicine (1), 5,21-dihydrorhazinilam-N-oxide (2), 3,14-dehydroleuconolam (3), and leuconodines A–E (4–8). The structures of these alkaloids were determined using NMR and MS analyses and in some instances confirmed by X-ray diffraction analyses. Alkaloids 1, 5, and 7 showed only moderate to weak cytotoxicity toward KB cells (IC50 12–18 μg/mL), while 8 showed moderate activity in reversing MDR in vincristine-resistant KB cells.